Development of spreadsheet-based applications for analysis and design of reinforced concrete beam as a learning tool in the Departmet of Civil Engineering at Bali State Polytechnic - Suardika, I Nyoman; Intara, I Wayan; Yuni, Ni Kadek Sri Ebtha (Proceedings; 2020: The 2nd International Conference on Applied Science and Technology (iCAST) 2019 Proceeding, 2020)
This study aims to develop spreadsheet-based applications for the analysis and design of reinforced concrete beam structures as a tool in learning courses in Reinforced Concrete Structures in the Bali State Polytechnic Civil Engineering Department. Reinforced concrete is still one of the most widely used construction materials and is applied in the construction world, especially in Indonesia, which belongs to a region with a high level of seismic risk. The process of calculating reinforcement of reinforced concrete structures involves quite a number of stages. In the practice of classroom learning it is not uncommon for students to miscalculate at one or more stages that lead to inaccurate design results. The results of field trials on the use of applications developed in this study provide significantly better average scores for students who use the application compared to students who do not use the application.